Publications on International Economic Law 2013–2014 - Herrmann, Christoph; Krajewski, Markus; Terhechte, Jörg Philipp (Springer Science and Business Media Deutschland GmbH, 2015)
This chapter shall provide an overview of publications in the field of international economic law during 2013 and 2014. This selection cannot and does not claim to be complete but it gives an impression of the diversity and variety of topics shaping the large body of international economic law and its recent developments.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Foreign Direct Investment; International Investment; Investment Treaty; Outward Foreign Direct Investment; World Trade Organization